The Relationship Of The Role Of Family To Preventing The Risk Of Fall In The Elderly In Tangkahan Village Durian, Brandan Barat District Langkat District Year 2021 - Nur Hasanah; Siskawati Amri; Nanarita Tarigan; Siti Saodah (Science Midwifery, 2021)
The purpose of this research is to find outThe Relationship of the Role of the Family to the Prevention of Fall Risk in the Elderly in Tangkahan Durian Village, Brandan Barat District, Langkat Regency in 2021. Based on an initial survey conducted in Tangkahan Durian Village, Brandan Barat District, Langkat Regency, there were 66 elderly people living with their families over the age of 60 years. The results of interviews with families found about 13 elderly people who had experienced falls caused by several factors including: the elderly living at home alone because their children worked, getting older, muscle weakness in the elderly, slippery floors, poor lighting, placement of home furnishings. random stairs. The results obtained in this study are known that of the 66 respondents the majority of the patient's age was20-30years with a total of 28 people (42.4) and minorities at the age of< 20year with a total of 9 people (13.6). Of the 66 respondents, the majority were female with a total of 38 people (57.6) and the minority was male with a total of 28 people (42.4). Of the 66 respondents, the majority of the respondents were IRT with a total of 27 people (40.9) and the minority occupation of the respondents was Kariawan with a total of 7 people (10.6). The majority of respondents' education in SMA was 35 people (53.0%) and the minority who obeyed the education of elementary school respondents amounted to 3 people (4.5%). Of the 66 respondents, the majority of respondents who have relationships with the elderly as children are 36 people (54.5%) and the minority of respondents who have relationships with the elderly as grandchildren are 12 people (18.2%). Of the 66 respondents, the majority of good family roles amounted to 39 people (59.1%) and the role of adequate families amounted to 12 people (18.2%). Of the 66 respondents.